Neural Correlates of Fear of Movement in Patients with Chronic Low Back Pain vs. Pain-Free Individuals - Meier, Michael L.; Stämpfli, Philipp; Vrana, Andrea; Humphreys, Barry K.; Seifritz, Erich; Hotz-Boendermaker, Sabina (Frontiers in Human Neuroscience, 2016)
Fear of movement (FOM) can be acquired by a direct aversive experience such as pain or by social learning through observation and instruction. Excessive FOM results in heightened disability and is an obstacle for recovery from acute, subacute, and chronic low back pain (cLBP). FOM has further been identified as a significant explanatory factor in the Fear Avoidance (FA) model of cLBP that describes how individuals experiencing acute back pain may become trapped into a vicious circle of chronic disability and suffering. Despite a wealth of evidence emphasizing the importance of FOM in cLBP, to date, no related neural correlates in patients were found and this therefore has initiated a debate about the precise contribution of fear in the FA model. In the current fMRI study, we applied a novel approach encompassing 1) video clips of potentially harmful activities for the back as FOM inducing stimuli and 2) the assessment of FOM in both, cLBP patients (N = 20) and age- and gender-matched pain-free subjects (N = 20). Derived from the FA model, we hypothesized that FOM differentially affects brain regions involved in fear processing in patients with cLBP compared to pain-free individuals due to the recurrent pain and subsequent avoidance behaviour. The results of the whole brain voxel-wise regression analysis revealed that 1) FOM positively correlated with brain activity in fear-related brain regions such as the amygdala and the insula and 2) Differential effects of FOM between patients with cLBP and pain-free subjects were found in the extended amygdala and in its connectivity to the anterior insula. Current findings support the FOM component of the FA model in cLBP.